Reforming Local Government Roles and Apparatus Structure in Indonesia - Efendi, Tifani; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the evolving role of local governments and the structuring of regional apparatuses within the framework of regional autonomy in Indonesia. Guided by Law Number 23 of 2014 on Regional Government, decentralization has positioned local governments as key actors in delivering effective, efficient, and participatory public services. However, despite this expanded authority, the implementation of regional autonomy continues to face substantial challenges, particularly in the institutional structuring of local government apparatuses that often remain misaligned with the diverse needs and characteristics of each region. Employing a qualitative research design with a policy analysis approach, this study draws on secondary data from policy documents, government evaluation reports, and academic literature published between 2020 and 2024. The findings reveal a significant gap between the normative frameworks established by national regulations and the practical realities at the local level. Many regional apparatuses are structured rigidly, mirroring centralized bureaucratic models, which undermines their ability to respond effectively to local socio-economic dynamics. The study proposes an ideal role model for local governments that integrates three core functions: as facilitators of development, providers of public services, and enablers of community participation. Additionally, it recommends restructuring regional apparatuses based on principles of flexibility, responsiveness, and actual regional needs. Practical strategies include strengthening institutional capacity through targeted training, conducting periodic organizational evaluations, and fostering collaboration between central and local governments. These efforts are essential to ensure that decentralization not only transfers authority but also enhances governance quality, reduces regional disparities, and supports the achievement of inclusive and sustainable development goals across Indonesia.